Analisis Tindak Tutur Lokusi dalam Animasi Edukasi Sains pada Saluran YouTube “Dolewak” - Yulita Ariani Fahrunnissa; Revania Putri Utami; Alayanna Isar Paramitha; Deasy Antoneta Purba; Riska Amelia Putri; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Limpad Nurrachmad (Institut Nalanda, 2025)
Locutionary speech acts are speech acts that have the intention to complete something. The background of this research is because locutionary speech acts can affect how listeners understand information. This research aims to understand how we “read” the meaning behind the words conveyed in the YouTube channel “Dolewak” Science educational animation video. The approach used in this research is descriptive qualitative methodology research, in collecting data using the simak catat technique, then the analysis technique used pragmatic analysis technique and agih technique. From the analysis that has been done, 109 data were found, namely (1) speech acts that intend to tell a total of 35, (2) speech acts that intend to explain a total of 27, (3) speech acts that intend to ask a total of 24, (4) speech acts that intend to invite a total of 10, and (5) speech acts that intend to want a total of 13. The benefit of this research is to introduce the concept of locutionary speech acts to readers, especially those who are less familiar with the field of pragmatics.